Design and fabrication of go-kart chassis - Muhamad Aslam, Kamarudin (2012)
This thesis deals with the design and fabrication of go-kart chassis. The objective of this thesis is to design and fabricate a go-kart chassis of an electric go kart. The main problem is the cost for current go-kart chassis is too expensive so the project is decide to fabricate with a lower cost. The scopes identified chassis design should bear load of 150kg and the go-kart chassis must with floor dimension of chassis is 1400mmx830mm. There are many steps taken to design and fabricate this chassis. The first stage is did some literature review about the existing go-kart and go-kart chassis. Mostly current model of go-kart chassis is made from tubular pipe. Hence, this project is to modify the current model of go-kart chassis into a model that is easier to design, build and modify. Follow up with some designing and sketching. During this phase, three designs had been sketch to be as the design concepts. The structural three-dimensional solid modelling of go-kart chassis was developed by using Solid Works engineering drawing software. As for each design have their advantages and disadvantages. After done with design and sketch, conceptual process is done and design 3 has been chosen because this design is more advantageous than other two designs. Design 3 is lightweight and easier to design, build and modify. Some modification is done on design 3 where, the go-kart chassis is more space saving and the design has provided protection to the users to prevent the user from fall during drive the go-kart. Next stage after finalize the design, the project is continued with fabrication process. The fabrication process also undergoes many steps such as material marking, cutting, drilling, welding, grinding and finalizing the go-kart chassis by painting to make a go-kart chassis more interested. Thus, by finishing this project, the objective of the project is achieved. Finally, the conclusion about this project and the recommendations for the future plan also attached together with this thesis.